Spatial Arrangement and the Making of Cosmos in Huaulu Society - Muhammad Damm (Kawalu: Journal of Local Culture, 2016)
Abstract This is a study about spatial arrangement and cosmological order of Huaulu society in Seram Island,Eastern Indonesia. Research and data collection had been conducted by ethnography. The problem is derived from Valerio Valeri’s works on Huaulu spatial arrangement that is considered unfinished. In Huaulu, there are four basic directions recognizable to its people, namely rai, lau, roe, and ria—they can be translated respectively to South, North, East, and West. However, among several meanings associated to them, there is also association with the direction to the interior or mountain, the direction to the sea, the direction to the forest or “outside world”, and the direction to the village or “inside world”, respectively. By positing Huaulu village as point of reference, we can clearly see that the island interior is always situated in the South, whereas the sea is always situated in the North; hence, the translation forrai and lau is South and North. But, in respect of roe and ria, their translations are more problematic, since their connotations as “outside” and “inside” donot imply direct relation to East and West. Valeri left this problem unanswered by leaving us a question: why does in some context at Huaulu “outside” stand to “inside” as “East” stand to “West”? By answering this question, this article aims to complete the reconstruction of Huaulu spatial arrangement and cosmological order that had been started—and left unfinished—by Valeri more than three decades ago. The result is a basic geometrical order that underlies Huaulu cosmology. Keywords: Dual Organization, Earth and Heaven, Forest and Village, Gender Distinction, Huaulu, Kitchen and Verandah